Deepest known novel species of the genus Ophiuroglypha Hertz, 1927 (Echinodermata: Ophiuroidea) from the central rift zone, Philippine Sea - Hasitha Nethupul; Sabine Stöhr; Haibin Zhang (European Journal of Taxonomy, 2023)
A new species of brittle star was collected in 2021 by the manned submersible “Fendouzhe” from the central rift zone deep waters, Philippine Sea, at a depth of 7729 m. It is described as Ophiuroglypha fendouzhe sp. nov., and is distinguished from its congeners based on the following features: slender arms, separated dorsal and ventral arm plates, overlapping large disc scales, and distally contiguous radial shields. We provide comprehensive descriptions of the external morphological features, including characteristics of the arm skeleton, and a phylogenetic analysis based on COI sequences. The interspecific genetic distance variation in the genus Ophiuroglypha found in this study was 3.89% to 24.25%. The new species constitutes the deepest known record for the genus Ophiuroglypha.